Analysis of Ordinary and Advanced Level In-field Physics Teachers’ Qualification, Experience and Job Placement - Badmus, O. T.; Jita, L. C. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2022)
Ordinary and advanced level physics teachers have similar responsibilities in impacting the knowledge of physics among learners. These responsibilities are premised around qualification, experience and job placement. Teachers’ experience has a place in the literature to influence physics performance. The curriculum of both advanced and ordinary level physics is with similarities and occasioned differences with respect to content knowledge. However, are there differences in the qualification, experience and job placement between these two sets of teachers? In view of the foregoing, this study examined advanced and ordinary level in-field physics teachers distribution vis a vis qualification, experience and job placement with a view to aggregate data for decision making, as well as, report gender representation, establish drift and possible remediation in the field. Descriptive research of the survey type was employed with Physics Teachers Ordinary and Advanced Level Inventory (PTOALI) as the instrument to elicit data from 225 physics teachers across the three states under review. Similarities exist in teachers’ qualification at ordinary and advance levels. Experience of teachers at ordinary level were higher than those teaching advanced level curriculum. Underrepresentation of female physics teachers was found among the sample audience. Also, physics teachers are limited in number across the sampled schools and that female physics teachers are under-represented within the sampled respondents. This study concludes that more qualified physics teachers are needed across the three states under review. Experienced physics teachers are also required in advanced level schools. This study recommends training and recruitment of adequate number of qualified physics teachers to cope with the surging number of willing learners.